Vegetation Health Monitoring System for Smart Farm using NDVI Analysis - Sumek Wisayataksin; Nontaput Junta; Jirat Kuanpreeyawat (2022 19th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technology (ECTI-CON), 2022)
We adapt the technique of normalized difference vegetation index (NDVI) to smart farms for monitoring the health of plants remotely over the IoT network. The system consists of a camera with 2 filters attached. The first one is an RGB filter to capture the visible light image, whereas another one is an infrared range filter. Two images are taken from a camera module and analyzed on Raspberry Pi 4 before being transmitted the NDVI image to the webserver for remote controlling and monitoring. The experimental results from actual plants reveal that our methodology can distinguish the healthy and unhealthy plants easily and efficiently.
Keywords: Smart Agriculture and AI; Remote Sensing in Agriculture; Greenhouse Technology and Climate Control